The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1415-47572014000300017
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamics in the rat EGF gene promoter after partial hepatectomy

Abstract: Epidermal growth factor (EGF), a multifunctional growth factor, is a regulator in a wide variety of physiological processes. EGF plays an important role in the regulation of liver regeneration. This study was aimed at investigating the methylation level of EGF gene throughout liver regeneration. DNA of liver tissue from control rats and partial hepatectomy (PH) rats at 10 time points was extracted and a 354 bp fragment including 10 CpG sites from the transcription start was amplified after DNA was modified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…In the serum, the level of EGF is minimal, which increases after liver resection [39]. In the liver, however, hepatectomy is associated with a downregulation of EGF transcription [40,41]. Consistently, in our study, we found EGF was downregulated after hepatectomy, whereas lower EGF mRNA coincided with poor occludin staining in the liver after SHx, and higher EGF mRNA co-existed with hardly disturbed canalicular networks after PHx.…”
Section: Discussionsupporting
confidence: 90%
“…In the serum, the level of EGF is minimal, which increases after liver resection [39]. In the liver, however, hepatectomy is associated with a downregulation of EGF transcription [40,41]. Consistently, in our study, we found EGF was downregulated after hepatectomy, whereas lower EGF mRNA coincided with poor occludin staining in the liver after SHx, and higher EGF mRNA co-existed with hardly disturbed canalicular networks after PHx.…”
Section: Discussionsupporting
confidence: 90%
“…In general, genes with hypermethylation within their promotor region show inhibited or silenced expression, however recent studies have shown that there is a subset of genes whereby hypermethylation was associated with increased expression ( Rauluseviciute et al, 2020 ) and this is dependent on the sites of methylation in a locus ( Dhar et al, 2021 ). In terms of the hypermethylated pathways identified in our study, genes identified from the ERBB family, such as EGF, show a negative correlation of reduced mRNA expression with DNA methylation ( Li et al, 2014 ). This is also the case for genes involved in “dendrite morphogenesis”, such as SHANK2 ( Fu et al, 2020 ) and ALK ( Gomez et al, 2015 ) and “axogenesis” and “positive regulation of nervous system development” such as the Slit/Robo genes ( Zheng et al, 2009 ).…”
Section: Resultsmentioning
confidence: 83%
“…The functional importance of this form of epigenetic regulation during regeneration was first suggested by older studies showing that azacytidine, which inhibits DNA methyltransferase activity, suppresses regeneration under certain circumstances [72]. More recent studies are beginning to characterize the gene-specificity and functional importance of changes in liver DNA methylation during regeneration, e.g., by demonstrating regenerative changes in methylation of EGF [73] but not SOCS3 [74] and also by implicating DNA-methylation-based disruption of urokinase plasminogen activator expression in the anti-regenerative activity of the Hepatitis B virus X protein [75]. The possibility that changes in DNA methylation are metabolically regulated during liver regeneration has also been suggested, at least indirectly, by two observations: First, liver regeneration is impaired in mice genetically disrupted for expression of methionine adenosyl transferase 1A (Mat1a, [76]).…”
Section: Dna Methylationmentioning
confidence: 99%